Nitrogen addition mediates the effect of soil microbial diversity on microbial carbon use efficiency under long‐term tillage practices. (4th July 2022) - Zhang, Mengni; Li, Shengping; Wu, Xueping; Zheng, Fengjun; Song, Xiaojun; Lu, Jinjing; Liu, Xiaotong; Wang, Bisheng; Abdelrhmana, Ahmed Ali; Degré, Aurore
Abstract: Tillage practices can influence soil microbial carbon use efficiency (CUE), which is critical for carbon cycling in terrestrial ecosystems. The effect of tillage practices could also be regulated by nitrogen (N) addition. However, the soil microbial mechanism relating to N fertilizer effect on microbial CUE under no‐tillage (zero‐tillage) is still unclear. We investigated how N fertilizer regulates the effect of tillage management on microbial CUE through changing microbial properties and further assessed the impact of microbial CUE on particulate (POC) and mineral‐associated organic matter carbon (MAOC). For this we used a 16‐year field experiment with no‐tillage (NT) and conventional tillage (CT), both of which combined with 105 (N1), 180 (N2), and 210 kg N ha −1 (N3) N application. We found that microbial CUE increased with increasing N application rate. NT increased microbial CUE compared with CT in the 0–10 cm. The bacterial and fungal diversities of NT were higher than CT and N application decreased their diversities in 0–10 cm. The partial least squares path model showed that bacterial and fungal diversity had a significant influence on microbial CUE. Furthermore, POC and MAOC under NT were higher than CT and they also increased with increasing N application rate. It suggested that increasing microbial CUE induced by N application had the potential to increase POC and MAOC. Overall, this study highlights that N addition can alter the effect of soil microbial diversity on CUE, which further improves our understanding to explain and predict the fractions of SOC (i.e., POC and MAOC) in tillage systems.